Strategi Meningkatkan Kinerja Karyawan Melalui Pelatihan Dan Pengembangan Pada Pengadaian Kota Lubuk Linggau - Husaini, Abdil; Deri apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
human resources are one of the factors to achieve company goals. Increased human resources can be capital to face market competition. One of them is by increasing employee performance. Increased employee performace is influenced by a few factorcs, including g leadership, work environment, and word ability. This study aims to analyze the strategy for improving employee performance through training and development at Pegadaian in Lubuklinggau City. Employee performance plays a crucial role in the success and productivity of an organization, and effective training and development programs are essential to enhance individual competencies. A quantitative research method was employed by distributing structured questionnaires to employees across various departments. The data were analyzed using statistical techniques to examine the relationship between training, development, and employee performance. The results indicate that both training and development have a significant positive impact on employee performance. These findings suggest that continuous investment in employee capacity building is a strategic step toward optimizing organizational outcomes. The study provides valuable insights for management to design more effective human resource development programs.